Poland Transport Policy Note : Toward a Sustainable Land Transport Sector - World Bank (Washington, DC, 2013)
This Policy Note addresses strategic issues facing Poland s transport sector. Despite recent growth and integration within the European Union (EU), the overall quality and efficiency of transport infrastructure and services is still poor. About 40 percent of the national roads network, which carries the largest volume of people and goods among all transport modes, is in poor or unsatisfactory condition. The government and freight-logistics industry recognize the railway sector's low efficiency but not much has been achieved since the 2001 restructuring that separated the infrastructure company and operators. Low staff productivity - more than 40,000 employees managing 17,000 km of track - and almost no investment in signaling and IT systems modernization are still major constraints with important long-term consequences, affecting current railway performance. The scope of the Note is on land transport, mainly on national roads and railways with a priority on strategic issues requiring immediate actions. The Note addresses issues specific to single modes and those requiring policy-making coordination. The current chapter sets the study context and helps to understand better the drivers for the current state of the sector and policy orientation. This chapter explains the note s focus and its organization. Chapter 2 reviews the national road network with a focus on infrastructure efficiency and sustainability. Chapter 3 covers the railway sector with an emphasis on the various entities of the PKP Group and how the sector competes with roads. Chapter 4 addresses road safety in Poland with the human and economic costs of current situation. Chapter 5 looks at land transport emissions and derives most of its conclusions from a recent study on GHG emissions in Poland s transport sector. Chapter 6 reviews the current policy path and offers three alternative policy options. The direct and indirect impact of implementing each policy options is assessed and compared to the current situation with a focus on medium-term (2020) sustainability.